2004
DOI: 10.1093/jn/134.6.1432
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity Is Associated with Adverse Health Outcomes among Human Infants and Toddlers

Abstract: The U.S. Household Food Security Scale, developed with federal support for use in national surveys, is an effective research tool. This study uses these new measures to examine associations between food insecurity and health outcomes in young children. The purpose of this study was to determine whether household food insecurity is associated with adverse health outcomes in a sentinel population ages < or = 36 mo. We conducted a multisite retrospective cohort study with cross-sectional surveys at urban medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
344
0
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 490 publications
(374 citation statements)
references
References 40 publications
19
344
0
11
Order By: Relevance
“…Research has confirmed this finding with recent studies demonstrating that poverty, and the unmet basic needs that result from it, results in greater susceptibility to disease and poorer health across the life span. [3][4][5][6]23,[28][29][30][31][32][33][34][36][37][38] Despite numerous leaders in the field advocating for addressing social needs as part of primary care [9][10][11][12]39 and professional guidelines emphasizing the need to address social determinants, [13][14][15][16][17] there has been little evidence to help guide this practice. 27,40 A previous study by our group demonstrated that a similar system can lead to more discussion and referrals for family psychosocial problems by pediatric trainees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has confirmed this finding with recent studies demonstrating that poverty, and the unmet basic needs that result from it, results in greater susceptibility to disease and poorer health across the life span. [3][4][5][6]23,[28][29][30][31][32][33][34][36][37][38] Despite numerous leaders in the field advocating for addressing social needs as part of primary care [9][10][11][12]39 and professional guidelines emphasizing the need to address social determinants, [13][14][15][16][17] there has been little evidence to help guide this practice. 27,40 A previous study by our group demonstrated that a similar system can lead to more discussion and referrals for family psychosocial problems by pediatric trainees.…”
Section: Discussionmentioning
confidence: 99%
“…We decided to screen for these needs because of their high prevalence among urban families, 19,27 the public availability of community resources designed to address them, and previous research demonstrating the association of these needs with negative child outcomes. 23,[28][29][30][31][32][33][34] The WE CARE clinical screening instrument was adapted from a larger family psychosocial screening instrument with test-retest reliability of .92. 19 For the current study, the survey consisted of 12 questions designed to identify the 6 basic needs and determine whether mothers wanted assistance with each need (Supplemental Appendix).…”
Section: Study Arms We Carementioning
confidence: 99%
“…As described, the occurrence of food insecurity among families with young children has particularly serious developmental consequences for children. [14][15][16][17][18][19][20][23][24][25] Additionally, exposure to parental IPV is a risk factor for children's poor physical, emotional, behavioral, social, and cognitive functioning. 43,44 It is also a concern that the different sources of stress that children experience residing in violent households could lead to the intergenerational cycle of violence and food insecurity.…”
Section: Present Studymentioning
confidence: 99%
“…The negative health outcomes associated with food insecurity appear to be linked to both the poorer quality of the diet in food insecure households as well as the uncertain and unpredictable nature of the food environment. Studies find a higher risk of common mental health disorders (Hadley & Patil, 2006;Patel & Kleinman, 2003), seasonal weight loss, dietary change (Rose, 1999;van Liere, Ategbo, Den Hartog, & Hautvast, 1995) and overall poorer health among members of food insecure or food insufficient households (Casey, Szeto, Robbins, Stuff, Connell, Gossett et al, 2005;Cook, Frank, Berkowitz, Black, Casey, Cutts et al, 2004;Siefert, Heflin, Corcoran, & Williams, 2004). Anthropological studies of food insecurity also document a range of social responses to food insecurity including migration, borrowing from other households, and switching to less desirable foods (Dirks, 1980;Panter-Brick & Eggerman, 1997;Shipton, 1990).…”
Section: The Biosocial Consequences Of Food Insecuritymentioning
confidence: 99%